2011
DOI: 10.1111/j.1475-1313.2010.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical guidelines for clinical studies of human vision

Abstract: Statistical analysis of data can be complex and different statisticians may disagree as to the correct approach leading to conflict between authors, editors, and reviewers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 50 publications
(70 reference statements)
0
90
0
Order By: Relevance
“…In FACT 3 cd/m 2 , only three made the highest score and ten just made the entry level at 18 cpd. Skewness combined with only minor differences within the study group suggested the use of nonparametric methods for describing normal data (Armstrong et al 2011). In our study, the population was limited to the age group most relevant for medical selection to posi- tions with high visual demands, and all participants had visual acuity within the limits of acceptance to duty as a naval pilot.…”
Section: Discussionmentioning
confidence: 99%
“…In FACT 3 cd/m 2 , only three made the highest score and ten just made the entry level at 18 cpd. Skewness combined with only minor differences within the study group suggested the use of nonparametric methods for describing normal data (Armstrong et al 2011). In our study, the population was limited to the age group most relevant for medical selection to posi- tions with high visual demands, and all participants had visual acuity within the limits of acceptance to duty as a naval pilot.…”
Section: Discussionmentioning
confidence: 99%
“…A Friedman 2-way analysis of variance by ranks with multiple comparisons was used to evaluate differences in medians among the three days [32]. The residual standard deviation (r m ) with each test was computed with the data from the subjects who completed a total of 3 sessions (replicates).…”
Section: Reproducibilitymentioning
confidence: 99%
“…A Friedman 2-way analysis of variance by ranks with multiple comparisons was used to evaluate differences in medians among the three days. 41 The residual standard deviation ( with each test was computed with the data from the subjects who completed a total of 3 sessions (replicates). LoAs were estimated again considering models of exchangeable or linked replicates.…”
Section: Discussionmentioning
confidence: 99%